Block Diversity and Governance - Israelsen, Ryan; Schwartz-Ziv, Miriam; Weston, James (The Review of Corporate Finance Studies, 2025)
Abstract Governance practices differ significantly across blockholder types. Compared with financial blockholders, nonfinancial blockholders are six times more likely to identify as activists. A textual analysis of regulatory filings shows that nonfinancial blocks govern through customized governance actions, while financial blocks follow generic performance metrics. Furthermore, blockholdings drive an important limitation in using Russell index thresholds as an identification strategy. Manipulation of index weights by Russell is strongly correlated with nonfinancial block ownership, confounding previous research on passive ownership. Using both reduced-form and structural estimates, we find that the market expects greater value creation from the entry of a nonfinancial blockholder.